2018
DOI: 10.1002/sctm.17-0043
|View full text |Cite
|
Sign up to set email alerts
|

Quality-Quantity Control Culture Enhances Vasculogenesis and Wound Healing Efficacy of Human Diabetic Peripheral Blood CD34+ Cells

Abstract: Autologous endothelial progenitor cell (EPC) therapy is commonly used to stimulate angiogenesis in ischemic repair and wound healing. However, low total numbers and functional deficits of EPCs make autologous EPC therapy ineffective in diabetes. Currently, no known ex vivo culture techniques can expand and/or ameliorate the functional deficits of EPCs for clinical usage. Recently, we showed that a quality‐quantity culture (QQc) system restores the vasculogenic and wound‐healing efficacy of murine diabetic EPCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 38 publications
2
33
0
Order By: Relevance
“…Preclinical data showed that CD34 + cells represent a main subset of stem/progenitor cells in peripheral blood mononuclear cell transplants that potentiate neovascularization in the ischemic area (Schatteman et al, 2000), and improve blood perfusion (Li et al, 2010) and wound healing (Tanaka et al, 2018). In the present study, CD45 − /CD31 − /CD34 + comprised the majority of the SVF cells.…”
Section: Discussionsupporting
confidence: 53%
“…Preclinical data showed that CD34 + cells represent a main subset of stem/progenitor cells in peripheral blood mononuclear cell transplants that potentiate neovascularization in the ischemic area (Schatteman et al, 2000), and improve blood perfusion (Li et al, 2010) and wound healing (Tanaka et al, 2018). In the present study, CD45 − /CD31 − /CD34 + comprised the majority of the SVF cells.…”
Section: Discussionsupporting
confidence: 53%
“…Transplanted RACs initiated angiogenesis in host tissues in the same manner as in previously described ischemia disease models[21, 29, 30]. In vitro , rat QQMNC EPC-CFUs were increased, mostly with dEPC-CFUs, which are capable of forming “tube-like” structures.…”
Section: Discussionmentioning
confidence: 55%
“…In this regard, QQMNCs are considered a representative “regeneration-associated cell” (RAC) population for ischemia or regenerative organs. This therapeutic concept was evaluated by several animal experiments, involving hindlimb ischemia, acute ischemic kidney injury, and diabetic wound healing mouse models, which analyzed the potential of QQMNCs to induce recovery organ function[21, 29, 30].…”
Section: Discussionmentioning
confidence: 99%
“…The number of transplanted human CD34 + cells appeared to have a strong correlation with the blood perfusion index in the severe combined immunodeficiency mouse model [23]. In addition, the increased number of transplanted CD34 + cells improved the chance of wound healing [32]. Previous clinical studies suggested thatCD34 + cells should be used as quality control for transplants, and a total CD34 + cell count over 10 5 /kg body weight seemed appropriate [33].…”
Section: Discussionmentioning
confidence: 99%